2017
DOI: 10.1002/mc.22662
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear orphan receptor NR4A1 regulates β1‐integrin expression in pancreatic and colon cancer cells and can be targeted by NR4A1 antagonists

Abstract: β1-Integrin is highly expressed and is a negative prognostic factor for colon and pancreatic cancer patients and the gene plays a functional role in cell migration and invasion. In this study, we demonstrate that β1-integrin expression is regulated in pancreatic and colon cancer cells by the pro-oncogenic orphan nuclear receptor 4A1 (NR4A1, Nur77, TR3) and knockdown of this receptor by RNA interference decreases β1-integrin protein and mRNA expression, α5-integrin and also expression of β1-integrin-dependent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 50 publications
2
22
0
Order By: Relevance
“…We have also confirmed that NR4A1 plays a key role in breast cancer invasion where TGFβ induces nuclear export of NR4A1 which interacts with E3 ligase complex proteins to induce SMAD7 ubiquitination and degradation (20,21). We previously reported that NR4A1 was a negative prognostic factor for lung cancer patient survival and NR4A1 was a pro-oncogenic factor regulating lung cancer cell proliferation and survival (22), and this has also been observed in cell lines derived from other solid tumors (2330). Structure activity studies among a series of 1,1-bis(3’-indolyl)-1-(substituted phenyl)methane compounds showed that some of these analogs bound NR4A1 and in cancer cell lines, acted as NR4A1 antagonists (2230).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…We have also confirmed that NR4A1 plays a key role in breast cancer invasion where TGFβ induces nuclear export of NR4A1 which interacts with E3 ligase complex proteins to induce SMAD7 ubiquitination and degradation (20,21). We previously reported that NR4A1 was a negative prognostic factor for lung cancer patient survival and NR4A1 was a pro-oncogenic factor regulating lung cancer cell proliferation and survival (22), and this has also been observed in cell lines derived from other solid tumors (2330). Structure activity studies among a series of 1,1-bis(3’-indolyl)-1-(substituted phenyl)methane compounds showed that some of these analogs bound NR4A1 and in cancer cell lines, acted as NR4A1 antagonists (2230).…”
Section: Introductionmentioning
confidence: 94%
“…We previously reported that NR4A1 was a negative prognostic factor for lung cancer patient survival and NR4A1 was a pro-oncogenic factor regulating lung cancer cell proliferation and survival (22), and this has also been observed in cell lines derived from other solid tumors (2330). Structure activity studies among a series of 1,1-bis(3’-indolyl)-1-(substituted phenyl)methane compounds showed that some of these analogs bound NR4A1 and in cancer cell lines, acted as NR4A1 antagonists (2230). The most active compound 1,1-bis(3’-indolyl)-1-) p -hydroxyhenyl)methane (CDIM8; DIM-C-pPhOH) which acts as a nuclear NR4A1 antagonist (29) in lung and other cancer cell lines inhibited NR4A1-dependent pro-oncogenic genes/pathways (2230).…”
Section: Introductionmentioning
confidence: 94%
“…We hypothesized that Nr4a1 enrichment facilitates the recruitment of histone modifying enzymes at target genes to regulate long-lasting changes in transcription 15,33 . To test this, we measured the enrichment of Nr4a1 at Cartpt, a gene with delayed activation after 28-days of abstinence.…”
Section: Cocaine Regulated Nr4a1 Via Histone Modifications (Hptms)mentioning
confidence: 99%
“…In response to stimuli, Nr4a1 is upregulated and it is shuttled to the nucleus where it binds nerve-growth-factor inducible gene B (NGFI-B)responsive elements (NRBE) at target gene promoters 14 . Importantly, Nr4a1 regulates gene expression via recruitment of chromatin modifying enzymes, many of which are stable across abstinence 14,15 .…”
mentioning
confidence: 99%
“…Furthermore, treatment of pancreatic, colon and breast cancer cells with C-DIM-8 or DIM-C-pPhCO2Me resulted in an effect similar to the knockdown of Nur77, with reduced the expression of β1-integrin, migration and adhesion. A high expression of β1-integrin is a poor prognostic factor for patients with colon and pancreatic cancer, and this protein is important in cell migration and invasion ( 50 , 89 , 90 ). Additionally, treatment of rhabdomyosarcoma cells, and of ACHN and 786-O renal cell lines with C-DIM-8 and DIM-C-pPhCO2Me was shown to inhibit tumor cell growth and induce apoptosis ( 91 , 92 ).…”
Section: Compounds That Modulate the Regulation Of Nur77mentioning
confidence: 99%